Penyerapan Tenaga Kerja Pada Industri Kecil Di Kota Ambon - Esy Delia Lewaherilla (EKONOMI & SOSIAL, 2014)
This study aims to find out the influence of work capital, wage level, type of industry, and the interaction between business capital and type of business on labor employment in small industries in Ambon city.       The research used primary data obtained from a survey conducted from May to June 2013. The population included the industries of garment, food and handycraft. The samples were 139 respondents selected by using the purposive sampling method.       The data were analysed by using multiple regression analysis method. The results reveal that : (1) business capital has a positive and significant influence on labour employment, either directly or indirectly through production; (2) Wage level directly has negtive and significant influence on labour employment; but indirectly, wage level has positive and significant influence throught production.